Prospective controlled cohort study on the safety of a monophasic oral contraceptive containing nomegestrol acetate (2.5mg) and 17β-oestradiol (1.5mg) (PRO-E2 study): risk of venous and arterial thromboembolism. (2nd November 2021) - Reed, Suzanne; Koro, Carol; DiBello, Julia; Becker, Kerstin; Bauerfeind, Anja; Franke, Christian; Heinemann, Klaas
Abstract: Objective: To assess and compare the risk of venous thromboembolism (VTE) and arterial thromboembolism (ATE) in NOMAC-E2 users with levonorgestrel-containing combined oral contraceptive (COCLNG) users. Study design: This large, prospective, observational active surveillance study used a non-inferiority design. New users of NOMAC-E2 and COCLNG were recruited in 12 countries in Australia, Europe, and Latin America. Women were followed up directly and self-reported outcomes of interest were validated via treating physicians. The main outcome of interest was VTE, specifically deep venous thrombosis of the lower extremities (DVT) and pulmonary embolism (PE). Secondary outcomes included all VTE and ATE. Data on confounders were captured and independent blinded adjudication assessed the classification of events. Incidence rates, crude (HRcrude), and adjusted (HRadj) hazard ratios were calculated. Results: A total of 101, 498 women (49, 598 NOMAC-E2 users and 51, 900 COCLNG users) were enrolled and followed for up to 2 years (144, 901 WY of observation). NOMAC-E2 users had a higher mean age (31.0 ± 8.63 years) than COCLNG users (29.3 ± 8.53 years) but other baseline characteristics were similar between the cohorts. The main analysis comparing the risk of DVT of the lower extremities and PE in NOMAC-E2 users versus COCLNG users yielded an HRadj of 0.59 (95% CI, 0.25–1.35) (adjusted for age, BMI, family history of VTE, and current duration of use). The risk of all VTE and ATE was not higher in NOMAC-E2 users compared with COCLNG users. Conclusion(s): NOMAC-E2 use was not associated with a higher risk of VTE or ATE compared with COCLNG.